Antibiogram Profiles and Disinfectant Effectiveness on Bacterial Isolates in the Surgical Intensive Care Unit - Salwa Eltawaty,; Ahmed Kabbashi,; Tawfeek Altawaty,; Mariam Boukhushaym, (AlQalam Journal of Medical and Applied Sciences, 2024)
Although studying bacterial contaminants in intensive care units has become a common topic, it is still being studied because of its importance in preserving the lives of patients and healthcare workers, where there is an increasing rate of the emergence of new bacterial strains that acquire resistance to antibacterial drugs. This is the first study targeting the surgical Intensive Care Unit (ICU) at Al-Wahda Hospital, Derna City, Libya. Standard traditional methods and molecular techniques were used to isolate, identify, and study the antibiogram profiles against bacterial isolates found to contaminate inanimate surfaces inside the ICU. The study results proved that the study area was contaminated with nine different bacterial genera belonging to Gram-positive (54%) and Gram-negative (46%) bacteria. The broadest antibiotic in this study was the highest inhibition percentage in this study was from Imipenem 10µg followed by Levofloxacin 5µg which suppressed the growth of 80% and 70% of all tested isolates, respectively. Among the tested disinfectants, hydrogen peroxide (Oxydol 3%) controlled (50%) of the tested bacteria, whereas glutaraldehyde (Prodex 99%) showed no activity. Povidone Hydro alcohol (Iodine 10%) actively controlled (70%) of the tested isolates. Conclusion: This study concludes that the targeted ICU is contaminated with nine different bacterial genera that show varied resistance to the tested antibiotics and disinfectants, threaten patients' and health workers' lives, and recommend the search for alternative effective antibiotics and disinfectants. على الرغم من أن فحص الملوثات البكتيرية في وحدات العناية المركزة أصبح موضوعًا شائعًا، إلا أنه لا يزال قيد الدراسة نظرًا لأهميته في الحفاظ على حياة المرضى والعاملين في مجال الرعاية الصحية، حيث يوجد معدل متزايد لظهور سلالات بكتيرية جديدة تكتسب مقاومة للأدوية المضادة للبكتيريا. هذه هي الدراسة الأولى التي تستهدف وحدة العناية المركزة الجراحية في مستشفى الوحدة، مدينة درنة، ليبيا. تم استخدام الطرق التقليدية القياسية والتقنيات الجزيئية لعزل وتحديد ودراسة ملفات المضادات الحيوية ضد العزلات البكتيرية التي وجد أنها تلوث الأسطح غير الحية داخل وحدة العناية المركزة. أثبتت نتائج الدراسة أن منطقة الدراسة ملوثة بتسعة أجناس بكتيرية مختلفة تنتمي إلى البكتيريا إيجابية الجرام (54٪) وسلبية الجرام (46٪). كان المضاد الحيوي ذو الفعالية الأوسع نطاقًا في هذه الدراسة هو إيميبينيم 10 ميكروجرام يليه ليفوفلوكساسين 5 ميكروجرام والذي قمع نمو 80٪ و 70٪ من جميع العزلات المختبرة على التوالي. ومن بين المطهرات التي تم اختبارها، سيطر بيروكسيد الهيدروجين (أوكسيدول 3%) على (50%) من البكتيريا المختبرة، في حين لم يظهر الغلوتارالدهيد (برودكس 99%) أي نشاط. وسيطر كحول البوفيدون المائي (اليود 10%) بنشاط على (70%) من العزلات المختبرة. الاستنتاج: خلصت هذه الدراسة إلى أن وحدة العناية المركزة المستهدفة ملوثة بتسعة أجناس بكتيرية مختلفة تظهر مقاومة متفاوتة للمضادات الحيوية والمطهرات المختبرة، وتهدد حياة المرضى والعاملين الصحيين، وتوصي بالبحث عن مضادات حيوية ومطهرات بديلة فعالة